(untitled) (Philadelphia, 1997)
This volume is a comprehensive guide to the practice of veterinary dentistry and oral surgery. It is patterned along the lines of the American Veterinary Dental College program and provides protocols used by the American Animal Hospital Association. Many illustrations show both prophylactic and restorative procedures for feline and canine patients.Coverage begins with information on dental equipment, oral anatomy and physiology, and diagnostic procedures, including the oral examination, clinical oral pathology, and radiology. Subsequent chapters cover pedodontics, periodontology, oral surgery, fracture repair, endodontic therapies, operative and restorative dentistry, and orthodontics. Other chapters provide a thorough understanding of dental and oral disease in domestic felines, rodents, lagomorphs, exotic animals, and large animals. The book also includes a guide to marketing a veterinary dentistry practice; a directory of equipment manufacturers and distributors; a list of American National Standard and American Dental Association specifications; and a glossary.
Keywords: Veterinary dentistry